2017
DOI: 10.1021/acs.analchem.6b04834
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Chiral Chromatography as the Second Dimension in Two-Dimensional Liquid Chromatography Experiments

Abstract: Chromatographic separation and analysis of complex mixtures of closely related species is one of the most challenging tasks in modern pharmaceutical analysis. In recent years, two-dimensional liquid chromatography (2D-LC) has become a valuable tool for improving peak capacity and selectivity. However, the relatively slow speed of chiral separations has limited the use of chiral stationary phases (CSPs) as the second dimension in 2D-LC, especially in the comprehensive mode. Realizing that the recent revolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 77 publications
1
64
0
1
Order By: Relevance
“…Barhate et al. developed an RPLC × Chiral‐LC and Chiral‐LC × Chiral‐LC methods to study isomers of a synthetic pharmaceutical intermediate .…”
Section: Selection and Combination Of Selectivitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Barhate et al. developed an RPLC × Chiral‐LC and Chiral‐LC × Chiral‐LC methods to study isomers of a synthetic pharmaceutical intermediate .…”
Section: Selection and Combination Of Selectivitiesmentioning
confidence: 99%
“…This drastic reduction of the analysis time has made it possible to develop a chiral-separation method as 2 D in LC × LC separations. Barhate et al developed an RPLC × Chiral-LC and Chiral-LC × Chiral-LC methods to study isomers of a synthetic pharmaceutical intermediate [153].…”
Section: Chiral Chromatographymentioning
confidence: 99%
“…Enantiomer separation has been performed utilizing different analytical techniques such as GC, TLC, SFC, HPLC, and CE [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography and high performance liquid chromatography analysis of various optically active stationary phases are standard methods for determining pheromone concentrations. However, separating chiral molecules remains a challenge, and requires chiral stationery phase columns and careful chromatographic techniques …”
Section: Introductionmentioning
confidence: 99%
“…However, separating chiral molecules remains a challenge, and requires chiral stationery phase columns 16 and careful chromatographic techniques. 17,18 The sea lamprey (Petromyzon marinus) is a parasitic vertebrate in the Laurentian Great Lakes, whose invasion resulted in major ecological disaster. Pheromone communication in sea lamprey is increasingly well understood and it has been shown that they rely on pheromones during migration and reproduction.…”
Section: Introductionmentioning
confidence: 99%